Disturbance rejection performance analyses of closed loop control systems by reference to disturbance ratio. (March 2015) - Alagoz, Baris Baykant; Deniz, Furkan Nur; Keles, Cemal; Tan, Nusret
Abstract: This study investigates disturbance rejection capacity of closed loop control systems by means of reference to disturbance ratio (RDR). The RDR analysis calculates the ratio of reference signal energy to disturbance signal energy at the system output and provides a quantitative evaluation of disturbance rejection performance of control systems on the bases of communication channel limitations. Essentially, RDR provides a straightforward analytical method for the comparison and improvement of implicit disturbance rejection capacity of closed loop control systems. Theoretical analyses demonstrate us that RDR of the negative feedback closed loop control systems are determined by energy spectral density of controller transfer function. In this manner, authors derived design criteria for specifications of disturbance rejection performances of PID and fractional order PID (FOPID) controller structures. RDR spectra are calculated for investigation of frequency dependence of disturbance rejection capacity and spectral RDR analyses are carried out for PID and FOPID controllers. For the validation of theoretical results, simulation examples are presented. Highlights: This study presents a disturbance rejection control approach based on RDR. Control system is considered as superposition of two channel controls. RDR spectrum analyses are derived for PID and FOPID controllers. Simulation results were presented for the validation of RDR analyses.